2004
DOI: 10.1002/mrd.20020
|View full text |Cite
|
Sign up to set email alerts
|

Molecular cloning and expression analysis of vitellogenin in scallop, Patinopecten yessoensis (bivalvia, mollusca)

Abstract: The present study was undertaken to determine scallop vitellogenin (Vtg) cDNA sequence, to identify Vtg synthesizing cell, and to analyze the regulation of Vtg mRNA expression. Clones containing partial cDNA sequence of Vtg were isolated from cDNA library of the scallop ovary by immunoscreening with the anti-scallop vitellin (Vn) serum. The deduced amino acid sequence of the clone containing the longest cDNA insert (1,689 bp) was identified as a member of the lipid transport protein family and exhibited about … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
31
2

Year Published

2006
2006
2019
2019

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 68 publications
(36 citation statements)
references
References 21 publications
3
31
2
Order By: Relevance
“…In this study, neither mussels nor clams exhibited significant differences in the ALP concentrations between genders, conversely to the main idea that vitellogenin is produced specifically in females, as shown for vitellogenin protein and gene expression in other bivalves (Osada et al 2004). Seasonal studies using different bivalve molluscs have shown that ALP levels follow the same trend as the gametogenic cycle in females, with mature individuals having naturally higher ALP concentrations.…”
Section: Discussioncontrasting
confidence: 63%
“…In this study, neither mussels nor clams exhibited significant differences in the ALP concentrations between genders, conversely to the main idea that vitellogenin is produced specifically in females, as shown for vitellogenin protein and gene expression in other bivalves (Osada et al 2004). Seasonal studies using different bivalve molluscs have shown that ALP levels follow the same trend as the gametogenic cycle in females, with mature individuals having naturally higher ALP concentrations.…”
Section: Discussioncontrasting
confidence: 63%
“…In mature females, Vtg are generally synthesized in response to endogenous estrogens, such as 17ß-estradiol (E2), released into the bloodstream and then stored in developing oocytes. Studies have outlined that levels of E2 in molluscs display a seasonal alternation associated with the reproductive cycle and are synchronized with variations of oocyte diameter and assumed Vitellogenin mRNA levels from early vitellogenic stage to spawning stage (Matsumoto et al, 1997(Matsumoto et al, , 2003Osada et al, 2004;Ni et al, 2014). Ni et al (2014) in their study recorded several magnitude higher vitellogenins expression in the ovary of C. gigas in the maturation and ripeness stages than in the partially spent stage.…”
Section: Discussionmentioning
confidence: 93%
“…But there are only a few studies about genetic diversity of P. yessoensis species at DNA levels thus far, and the documents about P. yessoensis mostly focused on the molecular clone of P. yessoensis (Osada et al 2004;Sato and Nagashima 2001) and protein analyze (Sarashina and Endo 2001;Kim et al 2008).…”
mentioning
confidence: 98%